Acute otitis media-related facial nerve palsy in a child: a case report and a literary review - Massimo Luca Castellazzi; Sara Torretta; Giada Maria Di Pietro; Annaclara Ciabatta; Pasquale Capaccio; Luca Caschera; Paola Marchisio (Italian Journal of Pediatrics, 2023)
Abstract Background Acute otitis media has become a rare cause of facial palsy in children. A high index of suspicion is essential to achieve the diagnosis and to properly treat this condition to avoid permanent neurological sequelae. Case presentation A case of acute otitis media-related facial nerve palsy in an 18 months-old child is described and a review of the recent literature about the clinical presentation, diagnosis, and management of this condition is performed. Conclusions Facial paralysis is an uncommon complication of acute otitis media that requires appropriate care. As highlighted in our report, the treatment of facial nerve palsy secondary to otitis media should be conservative, using antibiotics and corticosteroids. The role of antiviral is still a matter of debate. Myringotomy and a ventilation tube should be added when spontaneous perforation of the tympanic membrane is not present. More aggressive surgical approach should be considered only when there is no significant improvement.